Peningkatan Hasil Belajar Passing Sepak Bola Melalui Permainan Pemburu Binatang (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the learning outcome approach passing through playing soccer Beast Hunter on fourth-grade students of SD Negeri Batuagung 1 Balapulang District of Tegal 2014. This study was conducted in PTK SD Negeri Batuagung 1 Balapulang District of Tegal, the samples in this study were fourth graders, amounting to 24 students. This research method is Classroom Action Research. This study uses 2 cycles. The results showed that the learning outcomes passing football played by using the approach of animals hunters have a positive impact as seen on mastery learning outcomes of students who exceed the predetermined KKM 75 has increased the mastery learning in the first cycle reaches 70.83%, while the second cycle mastery learning reaches 95.83%. It is concluded that learning football passing play tracker approach has a positive impact, which can improve learning outcomes, interest, and motivation to learn